A comparison of radiographic features between non-survivors and survivors from ICU. (2021) - Wu, Gang; Zhou, Shuchang
Abstract: The clinical and imaging data of 121 ICU patients with SARS-CoV-2 infection (63 survivors and 58 non-survivors) were retrospectively reviewed. The clinical results and radiographic features were compared between survivors and non-survivors. Compared with survivors, non-survivors were more likely to develop ARDS (53 [91 %] vs. 22 [35 %], P < 0.0001), shock (6 [10 %] vs. 0, P = 0.009), cardiac injury(18 [31 %] vs. 6 [10 %], P = 0.003), acute kidney injury(21 [36 %] vs. 10 [16 %], P = 0.01), and pneumothorax(5 [9%] vs. 0, P = 0.017). There were typical radiographic features for ICU patients with SARS-CoV-2 pneumonia. Extensive air-space opacities could be seen in all patients. Middle and lower lung involvement was significantly more serious than upper lung (score 6.8 ± 1.9, 7.2 ± 2.1, and 5.7 ± 1.7, respectively, P < 0.0001). Based on X-ray involvement score, non-survivors were in a more critical condition than survivors (20.3 ± 4.6 vs. 19.1 ± 3.1, P = 0.038).